2017
DOI: 10.3390/en10101657
|View full text |Cite
|
Sign up to set email alerts
|

Grid-Connected Control Strategy of Five-level Inverter Based on Passive E-L Model

Abstract: At present, the research on five-level inverters mainly involves the modulation algorithm and topology, and few articles study the five-level inverter from the control strategy. In this paper, the nonlinear passivity-based control (PBC) method is proposed for single-phase uninterruptible power supply inverters. The proposed PBC method is based on an energy shaping and damping injection idea, which is performed to regulate the energy flow of an inverter to a desired level and to assure global asymptotic stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Assuming that y (11) is true. It can be concluded that the system satisfies the strict passive inequality, and therefore, this system can adopt PBC method 37 .…”
Section: Proposed Pbc Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Assuming that y (11) is true. It can be concluded that the system satisfies the strict passive inequality, and therefore, this system can adopt PBC method 37 .…”
Section: Proposed Pbc Modelmentioning
confidence: 99%
“…If there is a semi-definite and continuously differentiable storage function H(x) and a positive definite function Q(x) for ∀t > 0, the dissipation inequality is satisfied 37 :…”
Section: Proposed Pbc Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the predicted value of the grid impedance is difficult to ascertain. It is well known that the passivity‐based control method is based on energy shaping and damping injection idea by using the energy dissipation properties of the system under consideration . However, in existing passivity‐based control methods, there is no analytical robustness study which investigates the influence of parameter variations on the output voltage and the global stability.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the passivity-based control method is based on energy shaping and damping injection idea by using the energy dissipation properties of the system under consideration. 13 However, in existing passivity-based control methods, there is no analytical robustness study which investigates the influence of parameter variations on the output voltage and the global stability. The aforementioned control methods offer various advantages and disadvantages related to dynamic response, robustness against parameter variations, steady-state error, and stability.…”
Section: Introductionmentioning
confidence: 99%